The effect of the project based learning (PjBL) model on student’s learning outcome of UPT SMA Negeri 16 Muara Enim - Anwar, Yenny; Meilinda, M; Rosfa, Asti Zuhana (Universitas Negeri Jakarta, 2024)
One of the learning models that is currently strongly advised to be used in the learning process is Project Based Learning (PJBL). The purpose of this study is to ascertain how PJBL affects students' learning outcomes in the digestive system. Students (n=61) from Muara Enim, Indonesia's class XI Science public senior high school served as the research subjects. A quasi-experimental design with a non-equivalent control group is the study methodology employed. Project assignments, surveys, and observation sheets served as the tools. The independent sample t-test in the statistical program for social science 28 (SPSS version 28) was used to assess learning outcomes data. With a gain of 33.6 and n-gain of 0.63, the study's findings show that using the PjBL learning paradigm enhances students' learning outcomes. PjBl can increase motivation, and as it uses real-world challenges, strong curiosity will impact learning outcomes.